Analisis Efektivitas Pemungutan Pajak Bumi dan Bangunan Perkotaan dan Pedesaan (PBB-P2) di Kecamatan Kemayoran Jakarta Pusat - Adin Dahuri; Dwikora Harjo; Yani Yani; Fredetrica Linia Ariella (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
: in the last 4 (four) years PBB revenue has always failed to meet the predetermined PBB target of reaching 100%. This shows that there are still some taxpayers who do not make their PBB payments due to a lack of awareness from the community. Methods : This research uses descriptive qualitative methods. Collecting data from this research is by observation, interviews and documentation. The location: of this research is Kemayoran District, DKI Jakarta. The result : of the research shows that PBB collection has not reached the target in the last 4 years. Obstacles faced are still many taxpayers who delay paying PBB due to cost constraints and there are still many who do not understand the benefits of paying PBB. The author can conclude that PBB revenue has great potential to be developed by the provincial government in increasing the regional tax revenue of DKI Jakarta Province